Motivational interviewing for the prevention of alcohol misuse in young adults - Moreira, Teresa (2019)
Background Alcohol use and misuse in young people is a major risk behaviour for mortality and morbidity. Motivational interviewing (MI) is a popular technique for addressing excessive drinking in young adults. Objectives To assess the effects of motivational interviewing (MI) interventions for preventing alcohol misuse and alcohol‐related problems in young adults. Search methods We identified relevant evidence from the Cochrane Central Register of Controlled Trials (CENTRAL) (2015, Issue 12), MEDLINE (January 1966 to July 2015), EMBASE (January 1988 to July 2015), and PsycINFO (1985 to July 2015). We also searched clinical trial registers and handsearched references of topic‐related systematic reviews and the included studies. Selection criteria We included randomised controlled trials in young adults up to the age of 25 years comparing MIs for prevention of alcohol misuse and alcohol‐related problems with no intervention, assessment only or alternative interventions for preventing alcohol misuse and alcohol‐related problems. Data collection and analysis We used the standard methodological procedures expected by Cochrane. Main results We included a total of 84 trials (22,872 participants), with 70/84 studies reporting interventions in higher risk individuals or settings. Studies with follow‐up periods of at least four months were of more interest in assessing the sustainability of intervention effects and were also less susceptible to short‐term reporting or publication bias. Overall, the risk of bias assessment showed that these studies provided moderate or low quality evidence. At four or more months follow‐up, we found effects in favour of MI for the quantity of alcohol consumed (standardised mean difference (SMD) −0.11, 95% confidence interval (CI) −0.15 to −0.06 or a reduction from 13.7 drinks/week to 12.5 drinks/week; moderate quality evidence); frequency of alcohol consumption (SMD −0.14, 95% CI −0.21 to −0.07 or a reduction in the number of days/week alcohol was consumed from 2.74 days to 2.52 days; moderate quality evidence); and peak blood alcohol concentration, or BAC (SMD −0.12, 95% CI −0.20 to 0.05, or a reduction from 0.144% to 0.131%; moderate quality evidence). We found a marginal effect in favour of MI for alcohol problems (SMD −0.08, 95% CI −0.17 to 0.00 or a reduction in an alcohol problems scale score from 8.91 to 8.18; low quality evidence) and no effects for binge drinking (SMD −0.04, 95% CI −0.09 to 0.02, moderate quality evidence) or for average BAC (SMD −0.05, 95% CI −0.18 to 0.08; moderate quality evidence). We also considered other alcohol‐related behavioural outcomes, and at four or more months follow‐up, we found no effects on drink‐driving (SMD −0.13, 95% CI −0.36 to 0.10; moderate quality of evidence) or other alcohol‐related risky behaviour (SMD −0.15, 95% CI −0.31 to 0.01; moderate quality evidence). Further analyses showed that there was no clear relationship between the duration of the MI intervention (in minutes) and effect size. Subgroup analyses revealed no clear subgroup effects for longer‐term outcomes (four or more months) for assessment only versus alternative intervention controls; for university/college vs other settings; or for higher risk vs all/low risk participants. None of the studies reported harms related to MI. Authors' conclusions The results of this review indicate that there are no substantive, meaningful benefits of MI interventions for preventing alcohol use, misuse or alcohol‐related problems. Although we found some statistically significant effects, the effect sizes were too small, given the measurement scales used in the included studies, to be of relevance to policy or practice. Moreover, the statistically significant effects are not consistent for all misuse measures, and the quality of evidence is not strong, implying that any effects could be inflated by risk of bias.